Rational and ethical use of topical corticosteroids based on safety and efficacy - Sanjay K Rathi; Paschal D'Souza (Wolters Kluwer Medknow Publications, 2012)
Topical corticosteroids (TC) have greatly contributed to the dermatologist's ability to effectively treat several difficult dermatoses. The available range of formulations and potency gives flexibility to treat all groups of patients, different phases of disease, and different anatomic sites. However, the rapid rise in incidence of improper use of these drugs by dermatologists, general physicians, and patients threatens to bring disrepute to the entire group of these amazing drugs. Responsibility to disseminate proper knowledge regarding when, where, and how to use TC both to internists and patients rests primarily with the dermatologist. Benefits of rational and ethical use and the harm of overuse and misuse for nonmedical, specially for cosmetic purposes, should be clearly conveyed before penning a prescription involving TC. Simultaneous efforts to use political, legal, and other institutions to prevent misuse of these drugs by rationing their availability only through proper prescriptions will greatly help the cause. This will hopefully bring down both the extremes of ever increasing cases of steroid-induced dermatoses on one hand and the irrational fears of using TC in well justified indications on the other.